Persaingan Usaha Warung Tradisional dengan Toko Modern - Mardhiyah, Ainun; Safrin, Feby Aulia (Jurnal Bisnis dan Manajemen, 2021)
The development of modern retail activities in Indonesia is currently experiencing rapid development. The types of retail trade are divided into two, namely modern retail such as supermarkets, hypermarts and minimarkets and others, while traditional retail, namely traditional stalls that are managed privately, may also absorb workers. This research was conducted in Medan City, especially in Medan Helvetia District. This research was conducted to the owners of traditional stalls with the aim of knowing what factors can affect business competition between traditional stalls and modern shops. The Medan Helvetia District area was used as the research location because Helvetia District is one of the sub-districts in Medan City where most of the residents live in the retail business (in this case traditional stalls). The method or approach used in this research is descriptive with a qualitative approach. The results obtained are the factors that influence business competition between traditional stalls and modern shops, namely price, location, service and product completeness. The existence of modern shops has no effect on traditional stalls because they pay attention to competitive strategies, namely by paying attention to price, location, service and product completeness.Â